2008
DOI: 10.1002/ijc.24000
|View full text |Cite
|
Sign up to set email alerts
|

HPV16/18 vaccination to prevent cervical cancer in The Netherlands: Model‐based cost‐effectiveness

Abstract: We evaluated the cost-effectiveness of HPV16/18 vaccination for girls aged 12 years in The Netherlands in addition to cervical cancer screening. For this purpose, we developed a simulation model that describes the relation between each of the high-risk human papillomavirus (hrHPV) types and cervical disease, allowing the occurrence of multiple type-specific infections. Model parameters were derived from Dutch cohort studies, including a large population-based screening trial, and from the national cervical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…As the design of the model by de Kok et al is comparable to that published by other research groups that estimated cost-effectiveness of HPV vaccination [1,2,14], comparable costeffectiveness ratios from these analyses would be expected. Indeed, if the only relevant ratio from de Kok et al at D 19,700 would be taken, the similarity is striking.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…As the design of the model by de Kok et al is comparable to that published by other research groups that estimated cost-effectiveness of HPV vaccination [1,2,14], comparable costeffectiveness ratios from these analyses would be expected. Indeed, if the only relevant ratio from de Kok et al at D 19,700 would be taken, the similarity is striking.…”
supporting
confidence: 63%
“…I conclude that the conclusion by de Kok et al is misleading, should be re-visited and would probably better be formulated as "In the Netherlands, HPV vaccination is likely to be cost-effective if compared with screening alone", and that is fully in line what other studies -with 2 of them in Vaccinerecently found [1,2,14].…”
supporting
confidence: 51%
“…Thirty-six articles including EEs focused on HPV vaccination strategies were considered eligible for analysis; 20 were then excluded, as they referred to non-EU settings. Therefore, 16 articles [18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were eligible. One of them lacked essential methodological transparency [20], so 15 were eventually selected comprising 24 EEs since 9 articles [21, 23-26, 30, 32-34] contained two separate analyses.…”
Section: Literature Searchmentioning
confidence: 99%
“…64 Based on a recently published cost-effectiveness analysis of vaccination against human papillomavirus, the vaccine administration cost was assumed at €6.00 ($8.40). 65 Thus, the total immunization cost of a new pertussis vaccination strategy was assumed to be €24.30 ($33.40) per dose. For the at-birth immunization strategy, vaccination costs might be lower because midwives are already present during birth and administration might be relatively easy.…”
Section: Vaccination Costsmentioning
confidence: 99%